2022
DOI: 10.3390/land11030364
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Representation of Climate Change Adaptation Behaviour in New Zealand’s Forest Growing Sector

Abstract: To provide the forest industry with a better understanding of alternatives to simulate future adaptation pathways under evolving climatic and socio-economic uncertainty, we review the literature on how adaptation decisions are modelled in the context of plantation forests. This review leads to the conclusion that the representation of adaptation behaviour and decision-making remain very limited in most of the agent-based models in the forestry sector. Moreover, theoretical frameworks used to understand the ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 76 publications
(123 reference statements)
0
2
0
Order By: Relevance
“…A recent survey found that, in Aotearoa New Zealand, less than 10% of smallholder forest owners adopted adaptation strategies. 154 While there is high uncertainty for climate-related risks for plantation forestry, there are reasonable concerns over issues such as windthrow, particularly in densely planted stands, 155 and wildfire as the frequency of fire weather increases along the east coast of Aotearoa New Zealand. 156 These pose material risks to forestry companies and farm businesses with small forests, which have relevance for associated investors and creditors.…”
Section: Concept Proposal: Climate Resilience Loansmentioning
confidence: 99%
“…A recent survey found that, in Aotearoa New Zealand, less than 10% of smallholder forest owners adopted adaptation strategies. 154 While there is high uncertainty for climate-related risks for plantation forestry, there are reasonable concerns over issues such as windthrow, particularly in densely planted stands, 155 and wildfire as the frequency of fire weather increases along the east coast of Aotearoa New Zealand. 156 These pose material risks to forestry companies and farm businesses with small forests, which have relevance for associated investors and creditors.…”
Section: Concept Proposal: Climate Resilience Loansmentioning
confidence: 99%
“…However, most climate change research in forestry has focused on understanding the climate change impacts on ecological processes (Seidl et al 2016). In New Zealand, very little attention has been paid to climate change adaptation in managed production forests (Villamor et al 2022). As of 2019, around 1.7 million ha of plantation forests with an annual export value of $6.3 billion are exposed to climate change risks (MPI 2021b).…”
Section: Introductionmentioning
confidence: 99%